Raman Characterization of Carrier Concentrations of Al-implanted 4H-SiC with Low Carrier Concentration by Photo-Generated Carrier Effect - Tao Liu; Zongwei Xu; Mathias Rommel; Hong Wang; Ying Song; Yufang Wang; Fengzhou Fang (Crystals, 2019)
In this work, 4H SiC samples with a multilayer structure (shallow implanted layer in a lowly doped n-type epitaxial layer grown on a highly doped thick substrate) were investigated by Raman scattering. First, Raman depth profiling was performed to identify characteristic peaks for the different layers. Then, Raman scattering was used to characterize the carrier concentration of the samples. In contrast to the conventional Raman scattering measuring method of the Longitudinal Optical Plasmon Coupled (LOPC) mode, which is only suitable to characterize carrier concentrations in the range from 2 × 1016 to 5 × 1018 cm−3, in this work, Raman scattering, which is based on exciting photons with an energy above the band gap of 4H-SiC, was used. The proposed method was evaluated and approved for different Al-implanted samples. It was found that with increasing laser power the Al-implanted layers lead to a consistent redshift of the LOPC Raman peak compared to the peak of the non-implanted layer, which might be explained by a consistent change in effective photo-generated carrier concentration. Besides, it could be demonstrated that the lower concentration limit of the conventional approach can be extended to a value of 5 × 1015 cm−3 with the approach presented here.